2018
DOI: 10.1057/s41599-018-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of care labour, gender and work for men who teach young children

Abstract: This paper explores five Irish male primary teachers' daily experiences of care labour and gender in contemporary Irish schools. Taking a feminist poststructural approach, the study employs three data-collection phases using the interview as the primary method of enquiry. It employs a voice-centred relational method of data analysis, which involves four readings of data with each reading troubling the data in different ways. This paper places specific focus on three everyday phenomena: care, emotions and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was suggested that there has been a partial shift in society from hegemonic to ‘caring masculinity’, but research into the experiences of adult male carers has shown that the concept of caring remains ‘intimately bound up with female identity’ (Hunter et al, 2017; Gollins, no date, p. 7). Similarly, care work involving emotions continues to be perceived as an essentially feminine act (O'Keeffe, 2018). Thus, young men are still expected to demonstrate stereotypical masculinity (Robb & Ruxton, 2018), which devalues caring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that there has been a partial shift in society from hegemonic to ‘caring masculinity’, but research into the experiences of adult male carers has shown that the concept of caring remains ‘intimately bound up with female identity’ (Hunter et al, 2017; Gollins, no date, p. 7). Similarly, care work involving emotions continues to be perceived as an essentially feminine act (O'Keeffe, 2018). Thus, young men are still expected to demonstrate stereotypical masculinity (Robb & Ruxton, 2018), which devalues caring.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, young men are still expected to demonstrate stereotypical masculinity (Robb & Ruxton, 2018), which devalues caring. Indeed, men's sexuality may be questioned if they demonstrate femininity through nurturance and care; yet, their caring skills are doubted when they display masculinity via emotional distance and control (O'Keeffe, 2018). A wider debate is therefore needed in society in relation to the benefits for young men of talking about caring for themselves and others, but also ‘doing’ care.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the research on men in feminized occupations is less abundant than studies on women in masculinized occupations. The major part of the existing research (Simpson, 2009;O'Keeffe, 2018;Galley, 2020) focuses on men in care work, as this is considered a stereotypically 'feminine' task, both in private and in occupational contexts. Simpson describes her book on men in feminized occupations as a book 'about men who serve and care' (Simpson, 2009: 3), which seems to be a good identifier of the majority of 'feminine' occupations.…”
Section: Occupational Gender Minoritiesmentioning
confidence: 99%